Acute Esophageal Necrosis or Black Esophagus in the Setting of Diabetic Ketoacidosis - Saqr Alsakarneh MD; Fouad Jaber MD; Anika Mittal BA; Saeed Abughazaleh MD; Yazan Abboud MD; John Campbell MD (SAGE Publishing, 2023)
Acute esophageal necrosis (AEN) or black esophagus is a rare cause of mortality in patients with gastrointestinal bleeding. We present a case of a 54-year-old female who presented with diabetic ketoacidosis (DKA) and developed melena eventually attributed to AEN. The esophagogastroduodenoscopy (EGD) identified severe inflammation with black discoloration consistent with acute esophageal necrosis in the middle and lower esophagus. The patient was managed with intravenous pantoprazole and total parenteral nutrition (TPN) until she was able to tolerate an adequate diet. Black esophagus should be added to the differential diagnosis of patients with DKA who develop gastrointestinal bleeding. This need is stressed by the fact that early treatment is essential to reducing complications and mortality associated with the condition.